‘Forging healthy communities’: a service evaluation of a 12-week community-based exercise, nutrition, behaviour change and peer-support programme - Callum Leese; Blair H. Smith; Rosina Cross; Emma J. Cockcroft; Cassie Higgins (BMC Public Health)
Abstract Background Physical inactivity is a leading cause of premature mortality and morbidity worldwide. Primary care settings provide an opportunity for effective lifestyle interventions, including physical activity (PA) promotion. This study aims to evaluate the impact of a rural community-based multi-component, 12-week exercise, nutrition, education and peer-support programme on participants health and wellbeing. Methods This retrospective service evaluation included patients referred to the programme between January 2020 and December 2022 from primary care settings. Quantitative data (including body composition measures, mental wellbeing and patient activation) were collected at the entry and exit of the 12-week program. Participants also self-reported healthcare attendance in the 3 months prior to the baseline and post-intervention data-collection. Results Of the 424 people who participated in the programme, 84.7% (n = 359) indicated that they had achieved their goals. Significant improvements in BMI, weight, blood pressure, wellbeing, patient activation, muscle mass, body-fat mass and reduced healthcare attendance over a 12-week intervention were identified by repeated measure ANOVA. Post-hoc tests with a Bonferroni correction found that younger participants were significantly more likely to decrease their BMI and increase their mental wellbeing (as measured by WEMWBS) over the course of the programme. Higher attendance at the programme was also associated with greater reductions in BMI and greater improvements in patient activation. Discussion The findings support the effectiveness of multicomponent community-based exercise, nutrition, education and peer support interventions in improving health outcomes and reducing healthcare utilisation. Further research is needed to evaluate the long-term health outcomes of the education-exercise referral programme, across settings, and its potential to contribute to a sustainable healthcare system.